Evaluation of turbulence models in predicting wind loads on ground-mounted solar panels - Bernales, Francis Jenner T.; Pacer, Jihan S.; Hernandez, Jaime Y. Jr. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
Solar farms are developed in open terrain to get unobstructed sunshine for the solar panels, resulting to more efficient power conversion. In turn, solar panels are exposed to wind which could cause possible structural and mechanical damage. The lack of clear guidelines in designing solar panel systems against wind loads brings challenges in optimization of structural components and assurance of structural integrity. In this study, a computational fluid dynamics (CFD) model was developed using ANSYS R15.0 to predict wind loads and effects on a stand-alone ground-mounted solar panel. Four (4) turbulence models - Standard k-ɛ, Standard k-ω, Shear Stress Transport (SST) k-ω, and BSL Reynolds Stress Model (BSL RSM) - were evaluated based on the experimental data by Samani et al. (2016) and Abiola-Ogedengbe (2015). Based from the comparison of turbulence models with the wind tunnel test results of Samani et al. (2016), SST k-o showed better fit compared to the other turbulence models. From the generated CFD model, it was observed that the pressure distribution is symmetric about the center line for 0° and 180° winds. The critical drag and lift forces in the solar panel structure also occurred for 0° and 180° wind directions. The shape of the pressure distribution for 45° and 135° indicates the existence of corner vortices, with the higher equivalent net pressure occurring for 135°. Simulations were also performed using local wind conditions from the selected site at Calatagan Solar Farm, Batangas, with the associated wind parameters for the area indicated in NSCP 2015. Aerodynamic load coefficients were also determined, which can be useful for designing or assessing the solar panel structure inclusive of the panel support elements. Compared with the previous simulation, the load coefficients using local wind parameters were 18-29% higher, with the oblique wind directions being more sensitive to this change in wind conditions. Overall, the numerical simulations produced results that are on the conservative side, which can be adequate in the absence of wind tunnel test results. Transient simulations, however, are recommended in the future for this particular model and setup due to evident resonance and other dynamic effects, which need to be accounted for as well to obtain a more accurate CFD
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Wind-pre.; Turbu; Photovoltaic power sy